2021
DOI: 10.21037/jtd-20-2327
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of the Dumon stent for benign tracheal stenosis: a meta-analysis

Abstract: Background: The short-term efficacy of Dumon stent has been well demonstrated. Across years, however, due to insufficient sample size and absent of the randomized controlled trial, no reliable conclusion could be reach for Dumon stent's long-term efficacy. So, we conducted the first meta-analysis to evaluate the longterm efficacy and safety of the Dumon stent for benign tracheal stenosis.Methods: Data on related trials were obtained by doing a literature search in PubMed, Web of Science and Cochrane Library. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…However, our meta-analysis has limitations. In line with the heterogeneity that characterized these observational studies [197,198], a majority of included variables presented large I 2 values, indicating significant variations in terms of outcomes observed. Although we attempted to manage this by performing subgroup analysis and meta-regression by disease severity, the age of included patients, and genetic characteristics, the results could not fully explain the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 67%
“…However, our meta-analysis has limitations. In line with the heterogeneity that characterized these observational studies [197,198], a majority of included variables presented large I 2 values, indicating significant variations in terms of outcomes observed. Although we attempted to manage this by performing subgroup analysis and meta-regression by disease severity, the age of included patients, and genetic characteristics, the results could not fully explain the source of heterogeneity.…”
Section: Discussionmentioning
confidence: 67%
“…Stent placement is indicated in both intraluminal and extraluminal significant CAO and can be used in benign and malignant disease. Placing an airway stent is a difficult decision, and the operator must consider the benefit of its application, by preventing the airway re-occlusion, and also its disadvantages, mostly regarded with long-term associated complications [ 72 , 73 ]. There are two main types of airway stents concerning the material they are made of: tubular stents made of silicone and SEMS.…”
Section: Discussion On Cao Management and The Role Of Tracheal Stentsmentioning
confidence: 99%
“… 8 Recent reviews have shown effectivity rates of up to 75% for Dumon © stents treating benign tracheal stenosis. 9 , 10 Mucus retention has been described as frequently occurring complication, with a rate up to 24%, and results from mucosa injury after stent placement and tissue hyper granulation. 9 , 10 In our case, the patient suffered from severe mucus retention and the inability to clear his airway due to critical illness, advanced age, physical state, and comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Mucus retention has been described as frequently occurring complication, with a rate up to 24%, and results from mucosa injury after stent placement and tissue hyper granulation. 9 , 10 In our case, the patient suffered from severe mucus retention and the inability to clear his airway due to critical illness, advanced age, physical state, and comorbidity. Patient refused further treatment in order to prevent anticipated complications, prolonged hospitalization, and rehabilitation.…”
Section: Discussionmentioning
confidence: 99%